Relationships between presynaptic inhibition and static postural sway in subjects with and without diabetic neuropathy - Chun, Jihyun (J Phys Ther Sci, 2015)
[Purpose] Diabetic peripheral neuropathy can often lead to balance impairment. The spinal reflex is a mechanism that is reportedly important for balance, but it has not been investigated in diabetic peripheral neuropathy patients. Moreover, inhibitory or facilitatory behavior of the spinal reflex—known as presynaptic inhibition—is essential for controlling postural sway. The purpose of this study was to compare the differences in as presynaptic inhibition and balance in subjects with and without diabetic peripheral neuropathy to determine the influence of presynaptic inhibition on balance in diabetic peripheral neuropathy patients. [Subjects and Methods] Presynaptic inhibition and postural sway were tested in eight patients (mean age, 58±6 years) and eight normal subjects (mean age, 59±7 years). The mean percent difference in conditioned reflex amplitude relative to the unconditioned reflex amplitude was assessed to calculate as presynaptic inhibition. The single-leg balance index was measured using a computerized balance-measuring device. [Results] The diabetic peripheral neuropathy group showed lower presynaptic inhibition (47±30% vs. 75±22%) and decreased balance (0.65±0.24 vs. 0.38±0.06) as compared with the normal group. No significant correlation was found between as presynaptic inhibition and balance score (R=0.37). [Conclusion] Although the decreased as presynaptic inhibition observed in diabetic peripheral neuropathy patients may suggest central nervous system involvement, further research is necessary to explore the role of presynaptic inhibition in decreased balance in diabetic peripheral neuropathy patients.